2005
DOI: 10.1103/physrevb.72.214512
|View full text |Cite|
|
Sign up to set email alerts
|

Nodal quasiparticle lifetimes in cuprate superconductors

Abstract: A new generation of angular-resolved photoemission spectroscopy (ARPES) measurements on the cuprate superconductors offer the promise of enhanced momentum and energy resolution. In particular, the energy and temperature dependence of the on-shell nodal (kx = ky) quasiparticle scattering rate can be studied. In the superconducting state, low temperature transport measurements suggest that one can describe nodal quasiparticles within the framework of a BCS d-wave model by including forward elastic scattering and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 26 publications
(39 reference statements)
2
22
0
Order By: Relevance
“…The prefactor A is expected to be of order one 48 : numerical spinfluctuation calculations obtain A ¼ 2.4 for parameters relevant to optimally doped cuprates 50 ; fits to our CeCoIn 5 data give A ¼ 3.36. With these values so close, the charge dynamics of CeCoIn 5 seem to be consistent with a spin-fluctuation mechanism.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The prefactor A is expected to be of order one 48 : numerical spinfluctuation calculations obtain A ¼ 2.4 for parameters relevant to optimally doped cuprates 50 ; fits to our CeCoIn 5 data give A ¼ 3.36. With these values so close, the charge dynamics of CeCoIn 5 seem to be consistent with a spin-fluctuation mechanism.…”
Section: Discussionmentioning
confidence: 83%
“…In a d-wave superconductor, both regimes are expected to carry signatures of the nodal quasiparticle spectrum, namely, the linear energy dependence of the density of states [47][48][49][50] .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, one of our earlier studies reported that the spectral width in the nodal region was almost completely insensitive to the superconducting transition [3]. Theoretical studies indicate that in the superconducting state, phase space restrictions should result in a cubic dependence on T and ω [15].In the present letter, we focus on these issues again and show that the sample quality and experimental resolution are crucial factors in resolving "fine details" of the electronic structure near the nodal point. We show…”
mentioning
confidence: 69%
“…We have set (k, ω) = (1 − Z (k, ω))ω and E(k) is the bandstructure energy minus the chemical potential µ. For illustration, we will calculate Z (k, ω) = Z 1 (k, ω) + iZ 2 (k, ω) for a Hubbard model using a random phase approximation (RPA) for the spin-fluctuation interaction [19] (…”
Section: Random Phase Approximation Self-energymentioning
confidence: 99%